2014
DOI: 10.2147/opth.s71102
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapies for corneal perforations: 10 years of cases in a tertiary referral hospital

Abstract: PurposeTo report surgical therapies for corneal perforations in a tertiary referral hospital.MethodsThirty-one eyes of 31 patients (aged 62.4±18.3 years) with surgically treated corneal perforations from January 2002 to July 2013 were included in this study. Demographic data such as cause of corneal perforation, surgical procedures, and visual outcomes were retrospectively analyzed.ResultsThe causes of corneal perforation (n=31) were divided into infectious (n=8, 26%) and noninfectious (n=23, 74%) categories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 14 publications
1
79
0
3
Order By: Relevance
“…Despite other studies that have evaluated aetiologies or treatment in corneal perforations, our study extensively describes the causes, surgical therapies and outcomes in this scenario 1 4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite other studies that have evaluated aetiologies or treatment in corneal perforations, our study extensively describes the causes, surgical therapies and outcomes in this scenario 1 4…”
Section: Discussionmentioning
confidence: 99%
“…When the corneal perforation is larger in size, involving the corneal periphery, the treatment options are limited to tectonic grafts, where the corneal and/or scleral surfaces need to be restored 2 4 19 20. Hanada et al 12 reported that keratoplasty is a valuable option for maintaining ocular integrity and visual acuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these neurotrophic eyes, graft survival becomes problematic, and the same is expected for the implantation of biosynthetic corneal substitutes. (Bonini et al, 2003;Yokogawa et al, 2014).…”
Section: Neurotrophic Corneasmentioning
confidence: 99%
“…Placentas and fetal membranes have been successfully used for tissue engineering applications. For instance, amniotic membrane has been used to prevent adhesions [Kuriu et al, 2009;Petter-Puchner et al, 2011;Ellington and Ferguson, 2014], to repair recto-vaginal fistulas [Roshanravan et al, 2014], to treat skin burns and wounds [Taghiabadi et al, 2015] and chronic leg ulcers [Zelen et al, 2013], and for regeneration of corneal and conjunctival epithelium [Yokogawa et al, 2014;Zeng et al, 2014;Zhou et al, 2015], although it was ineffective for treatment of Mooren's ulcer, a rare but severe ulcerative keratitis [Schallenberg et al, 2013]. In addition, its anticancer properties have been noted, probably due to the downregulation of HSP90 (heat shock protein 90), cancer cell cycle arrest and inhibition of angiogenesis [Magatti et al, 2012;Niknejad and Yazdanpanah, 2014].…”
Section: Placental Ecm and Its Tissue Engineering Applicationsmentioning
confidence: 99%